DAMPAK PERUBAHAN MODAL SOSIAL TERHADAP PERUBAHAN SISTEM PENGOLAHAN SAMPAH DI YOGYAKARTA - Theresia Damai T.; Kusumastuti Kusumastuti; Isti Andini (ARSITEKTURA, 2015)
Badran village is a village that used to have a reputation as thugs village and face the problem of garbage. Over time, this village managed to overcome the problem of garbage with 3R-based waste management program. This success is motivated by changes in social capital and leadership as a catalyst in the presence of co-operation. Forms of social capital that result in changes in the waste management system RW 11 Kampung Badran is trust, norms and networks. The third form of social capital and the existence of aspects of leadership affects the sustainability of programs aimed at managing waste in RW 11, Kampung Badran. For that we need further review of how the influence of the three components of social capital that is trust, norms and networks of the waste management system. The method used the descriptive qualitative method with the presentation of narrative technique. Based on the method applied was found that all three forms of social capital affects the implementation of waste management activities in the form of bank program garbage, composting and manufacture craft of garbage. Trust influence the process of knowledge transfer of cadres to the citizens, norms affect the implementation of programs and networks organizing effect on the acquisition of outside resources. Keywords: social capital, trust, norms, network, 3R